Letter from James B. Guthrie to James Curtis Booth, May 17, 1854 - Guthrie, James (1854)
James B. Guthrie (1792 - 1869), United States Secretary of the Treasury from 1853-1857, informs James Curtis Booth (1810-1888) that the Treasury has been billed $100 for his order of three Evans Safety Guards.
Keywords: Guthrie, James, 1792-1869; Booth, James Curtis, 1810-1888; United States. Department of the Treasury; United States Mint; Mint of the United States